ANALISIS PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP NIAT BELI ULANG PRODUK WARDAH DI KOTA PONTIANAK (STUDI PADA WARDAH KOSMETIK DI KOTA PONTIANAK) - B31110038, NOVITA SARI (Jurnal Manajemen Update, 2015)
Strict Business competition is a big challenge for a company. As a quite long standing company, PT. Paragon Technologi and Innovation, introduced a beauty product named â€œWARDAHâ€. This product must be able to endure the image and quality of the product among the society. So, the better the image of the brand and the quality of the product, the higher the urge to buy Wardah Product.Sample from this research were from 100 respondents which gained by using Lemeshow technique. Data collecting technique was by spreading the questionnaire. Data analysis was done by doubled linear analysis which processed with SPSS program.The result of the research shows that brand image variable and quality product is positively and significantly influencing to the product of wardah cosmetic re-buy willingness. Key Words : Brand image, Quality product and Re-buy Willingness. Â